Development of Animation Media based on Multiple Representations in Colloid Flipped Classroom Learning - Ali Amirul Mu'minin; Nurul Zaizatu Musdalifah (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This research aims to develop and test the feasibility of an animation media based on multiple representations in colloid using flipped classroom learning. The type of this research is research and development with 4-D model (define, design, develop, and disseminate) which carried out up to the development stage (develop). The feasibility test of an animation video consists of material and media validity test and product trials. Data of feasibility test were analyzed using quantitative descriptive analysis. The results of the material and media validity tests were 82% and 83%, which indicates that the animation video was included in the very feasible criteria and the results of product trials were 85% which indicates that user responses were included in the very good criteria. The results of the feasibility test show that an animation media based on multiple representations was declared feasible for use in colloid flipped classroom learning.